Chapter 4 : Infrastructure - Gosling, Simon N.; Wood, Ruth (Chemist); Darch, Geoff; Powrie, William; Hughes, Paul N.; Bell, Sarah (Sarah Jayne); Watson, Geoff V. R.; Paulson, Kevin S.; Chapman, Lee, 1977-; Dawson, Richard (Civil engineer) (The University of Hull, 2016)
Increased frequency of flooding from all sources is the most significant climate change risk to UK infrastructure, including energy, transport, water, waste and digital communications. Assets and networks across all infrastructure sectors are already exposed to multiple sources of flooding, and the number of assets exposed could double under expected changes in climate by the 2080s. Coastal infrastructure is particularly at risk from storm surges and rising sea levels, as well as higher rates of coastal erosion in some areas. Infrastructure networks near rivers will also be increasingly at risk from projected higher flows and subsequent bankside erosion.